Microwave-assisted rapid preparation of Ca10Na(PO4)7 using sodium triphosphate as a phosphorus source. Issue 10 (December 2015) - Zhou, Huan; Zhang, Mingjie; Chai, Hong; Hou, Saisai; Tan, Meiling; Wang, Liqun; Bhaduri, Sarit B; Deng, Linhong
Abstract: As a potential orthopedic biomaterial, calcium sodium phosphate (CNP) represents a viable alternative to the quintessentially important β-tricalcium phosphate (β-TCP). The conventional solid-state synthesis of CNP requires extensive time and energy with ease of introduction of impurities and formation of coarse particles needing further comminution. The present work demonstrates a simple but versatile microwave assisted method to prepare CNP with negative zeta potential using sodium polyphosphate and calcium chloride as precursors. There are several important characteristics of the product. The as-synthesized CNP crystals showed two different morphologies- polygonal and whisker-like. The as-formed CNP was thermally stable without new phase nucleation after calcination at 1000 °C. This material promoted the proliferation of osteoblast cells as compared to HA in vitro. Additionally, the particles can be easily dispersed because of their negative zeta potential. Finally, the particles revealed their anti- Escherichia coli attachment potential. With all of these attributes, it is expected CNP can be a potential biomaterial in orthopedics and a good candidate for fabrication of composites with relevant biopolymer matrices.